2004
DOI: 10.1042/bj20040721
|View full text |Cite
|
Sign up to set email alerts
|

Brassica juncea 3-hydroxy-3-methylglutaryl (HMG)-CoA synthase 1: expression and characterization of recombinant wild-type and mutant enzymes

Abstract: 3-hydroxy-3-methylglutaryl (HMG)-CoA synthase (HMGS; EC 2.3.3.10) is the second enzyme in the cytoplasmic mevalonate pathway of isoprenoid biosynthesis, and catalyses the condensation of acetyl-CoA with acetoacetyl-CoA (AcAc-CoA) to yield S-HMG-CoA. In this study, we have first characterized in detail a plant HMGS, Brassica juncea HMGS1 (BjHMGS1), as a His6-tagged protein from Escherichia coli. Native gel electrophoresis analysis showed that the enzyme behaves as a homodimer with a calculated mass of 105.8 kDa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…BjHMGS1 (GenBank accession no. AAF69804) was cloned, expressed, and purified as described (11). The N-terminal hexahistidine tag was cleaved by thrombin digestion during overnight dialysis against 100 mM NaCl͞25 mM Hepes (pH 7.5) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BjHMGS1 (GenBank accession no. AAF69804) was cloned, expressed, and purified as described (11). The N-terminal hexahistidine tag was cleaved by thrombin digestion during overnight dialysis against 100 mM NaCl͞25 mM Hepes (pH 7.5) at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, detailed kinetic studies of wild-type and mutant forms of one of the four B. juncea HMGS (BjHMGS), BjHMGS1, demonstrated that (E,E)-11-[3-(hydroxymethyl)-4-oxo-2-oxytanyl]-3,5,7-trimethyl-2,4-undecadienenoic acid (F-244), alternatively known as 1233A, L-659,699, or hymeglusin, acts as a potent inhibitor with an IC 50 of 35 nM (8)(9)(10)(11)(12). F-244 is a polyketide from Fusarium sp.…”
mentioning
confidence: 99%
“…HMGR catalyzes the key regulatory step of the pathway in plants and in mammals. In addition, HMGS activity has been positively correlated with rubber production in Hevea brasiliensis, suggesting a regulatory role for this enzyme as well (Suvachittanont and Wititsuwannakul 1995;Nagegowda et al 2004). It has long been assumed that the DXP and MVA pathways are independently regulated.…”
Section: Introductionmentioning
confidence: 94%
“…The 3-hydroxy-3-methylglutaryl-coenzyme A synthase (HMGS, EC 2.3.3.10, formerly EC 4.1.3.5) catalyses the condensation of acetyl-CoA with acetoacetyl-CoA to form HMG-CoA in MVA pathway (Nagegowda et al 2004;Kai et al 2006). The HMG-CoA is then converted by HMGCoA reductase (HMGR) to yield MVA which is subsequently converted to IPP, the universal precursor for the synthesis of isoprenoids, including tanshinones.…”
Section: Introductionmentioning
confidence: 99%